DIPLOMASI INDONESIA DALAM MEMPERTAHANKAN JAMU SEBAGAI WARISAN BUDAYA NASIONAL - Pertiwi, Setya Ambar; Hidayat, Nurul (Moestopo Journal of International Relations (MJIR), 2024)
This research aims to answer how Indonesian Diplomacy Maintains Herbal Medicine as a National Cultural Heritage in 2021-2024. The research method used is a qualitative method with descriptive research type and data collection techniques through literature study from primary and secondary sources. This research uses the theories of cultural diplomacy and nationalism and cultural resilience. The results of the research found that Indonesian Diplomacy in preserving herbal medicine as an intangible cultural heritage is within domestic and international scope based on the 2021-2024 periodization. The concept of Intangible Cultural Heritage is categorized by UNESCO as an institution under the UN that ratifies and determines cultural heritage in Indonesia. Jamu, which is Indonesia's identity, must be maintained by promoting it through Cultural Diplomacy and preserving it by providing understanding through love for Indonesian products that is instilled with a sense of Nationalism and innovating herbal medicine so that it remains relevant to the times based on the theory of Cultural Resilience. Indonesia's implementation in maintaining herbal medicine as a national cultural heritage by means of student exchanges, modernizing the scientification of herbal medicine, emphasizing quality control of herbal medicine products in terms of packaging to standardizing distribution permits in the national and international realms, to fighting for rights by registering herbal medicine as a cultural heritage with UNESCO which takes 2 years to avoid cultural claims by other countries.